Subvisible (2–100 μm) particle analysis during biotherapeutic drug product development: Part 2, experience with the application of subvisible particle analysis. Issue 6 (November 2015) - Corvari, Vincent; Narhi, Linda O.; Spitznagel, Thomas M.; Afonina, Nataliya; Cao, Shawn; Cash, Patricia; Cecchini, Irene; DeFelippis, Michael R.; Garidel, Patrick; Herre, Andrea; Koulov, Atanas V.; Lubiniecki, Tony; et al.
Abstract: Measurement and characterization of subvisible particles (including proteinaceous and non-proteinaceous particulate matter) is an important aspect of the pharmaceutical development process for biotherapeutics. Health authorities have increased expectations for subvisible particle data beyond criteria specified in the pharmacopeia and covering a wider size range. In addition, subvisible particle data is being requested for samples exposed to various stress conditions and to support process/product changes. Consequently, subvisible particle analysis has expanded beyond routine testing of finished dosage forms using traditional compendial methods. Over the past decade, advances have been made in the detection and understanding of subvisible particle formation. This article presents industry case studies to illustrate the implementation of strategies for subvisible particle analysis as a characterization tool to assess the nature of the particulate matter and applications in drug product development, stability studies and post-marketing changes.